Correction of under-reaching in twin circuit parallel overhead lines without residual current input from the parallel line - Bin Abdullah M.F.; Mukerjee R.N.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Mutual coupling poses one of the most difficult problems witnessed during single phase to earth fault, in transmission line protection. In lines, on multiple circuit towers or on the same right of way, the zero-sequence circuits of the lines get mutually coupled causing an error in the apparent impedance seen by the relay. This causes the distance protection relay at one end of the faulty line to over-reach while the one at the other end to under-reach. Also, incorrect sensing of the ground fault due to zero-sequence voltage inversion caused by mutual coupling in the zero-sequence network may lead to false trip of the neighbouring healthy line. This paper presents a non-iterative microprocessor based algorithm, not requiring residual current measurement from the parallel circuit, for computing fault distance and zero sequence compensation in basic distance relaying scheme. 2006 IEEE.